A new species of Sicydium (Cucurbitaceae) from Argentina - Nicola, Marcela Viviana (2015)
We describe a new species of Sicydium endemic to Argentina. Relationships and differences with morphologically and geographically closest species are discussed, including a key for material with staminate flowers to all species of Sicydium, and an illustration of the new species.